APPLICATION OF PROJECT BASED LEARNING IN CHEMICAL ENGINEERING EDUCATION TO IMPROVE STUDENTS' PRACTICAL SKILLS - Martinus (Adisam Publisher, 2025)
Chemical engineering education is faced with the challenge of not only imparting theoretical knowledge, but also to develop students' practical skills that meet industry needs. Project Based Learning (PjBL) has been implemented as an effective approach to answer these challenges. This research aims to evaluate the effectiveness of PjBL in improving students' practical skills in the field of chemical engineering. Research is carried out through providing projects that are integrated with the curriculum and oriented to real industrial problems. The method used is comparative analysis of pre-test and post-test to measure improvement in practical skills. The results showed that students who took PjBL showed significant improvements in collaboration skills, problem solving, and use of technology. Apart from that, this approach also increases student motivation and involvement in the learning process. In conclusion, PjBL is an innovative and effective learning strategy that strengthens the practical skills of chemical engineering students and prepares them to become part of a competent workforce in the chemical industry.